Measurements in room acoustics Uncertainties and influence of the measurement position - Witew, Ingo B. (Aachener Beiträge zur Akustik, 2022)
Regardless of the field, measurements are essential for validating theories and making well-founded decisions. A criterion for the validity and comparability of measured values is their uncertainty. Still, in room acoustical measurements, the application of established rules to interpret uncertainties in measurement is not yet widespread. This raises the question of the validity and interpretability of room acoustical measurements. This work discusses the uncertainties in measuring room acoustical single-number quantities that complies with the framework of the ``Guide to the Expression of Uncertainty in Measurement''(GUM). Starting point is a structured search of variables that potentially influence the measurement of room impulse responses. In a second step, this uncertainty is propagated through the algorithm that determines single-number quantities. A second emphasis is placed on the investigation of spatial fluctuations of the sound field in auditoria. The spatial variance of the sound field in combination with an uncertain measurement position marks a major contribution to the overall measurement uncertainty. To reach general conclusions, the relation between changes in the measurement location and the corresponding changes in measured room acoustical quantities is investigated empirically in extensive measurement series. This study shows how precisely a measurement position must be defined to ensure a given uncertainty of room acoustical single-number quantities. The presented methods form a foundation that can be exibly extended in future investigations to include additional influences on the measurement uncertainty.